THE EFFECTIVENESS OF SIPD IN ENHANCING DEVELOPMENT PLANNING SYNERGY IN GORONTALO CITY - Ikram Muhammad; Taufik Adam; Moh Septiawan Ali (Governance: Jurnal Ilmu Administrasi Publik, 2024)
This study aims to analyze the effectiveness of the Regional Government Information System (SIPD) in supporting the synergy of development planning in Gorontalo City. A qualitative approach with a case study design was employed, utilizing data collection techniques such as in-depth interviews, observation, and documentation. The research informants included local government agencies and relevant stakeholders involved in the development planning process. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of SIPD has contributed to improving the integration of planning, budgeting, and development reporting in a more systematic and transparent manner. SIPD also enhances synergy among municipal, provincial, and central governments through policy alignment and data integration. However, its effectiveness has not been fully optimized due to technical constraints such as system stability and network access, as well as non-technical challenges including limited human resource capacity, data literacy, and institutional coordination. This study highlights that the effectiveness of SIPD is not solely determined by technological factors but also by organizational readiness, human resource capacity, and policy support. Therefore, optimizing SIPD requires a comprehensive approach through capacity building, strengthening technological infrastructure, and improving intergovernmental coordination. These findings provide empirical contributions to the development of data-driven governance and the enhancement of integrated development planning.